PECULIARITIES OF THE FORMATION OF ARCHITECTURAL AND PLANNING SOLUTIONS OF PASSENGER BUS STATIONS AND BUS STATIONS IN SMALL CITIES OF UKRAINE - Грінченко, Тетяна; Галак, Катерина; Малійова, Олександра (SWorldJournal, 2024)
In the article the questions of providing quality services are examined outwardly main motor transport of population of small cities, in the conditions of modern changes and expansion of connections, both in the field of access to the workplaces, to the